Peran Rezim Trans Pacific Partnership (TPP) dalam Mempengaruhi Kepatuhan Negara Anggota Terhadap Rezim Hak Kekayaan Intelektual (HAKI) Internasional (Studi Kasus : Software Piracy di Vietnam Tahun 2007-2010) - Adinda Gusty Rachmah; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2018)
Intellectual Property Right is a sensitive issue for developing country such as Vietnam. Accession to the Trans Pacific Partnership (TPP) at 2008 and approval TRIPS Agreement makes Vietnam engaged in a system to guarantee the protection of intellectual property rights. TPP is a free trade agreement that is projected to be a 'comprehensive and high standard free trade agreement' in the trans pacific region which aims to liberalize trade in almost all sectors of goods and services. This research aim to obtain an overview and analysis of the Trans Pacific Partnership (TPP) and its relation to the crime of intellectual property rights, explaining the implementation of TPP in Vietnam in overcoming intellectual property rights. International Cooperation theory and International Regime theory are used to explain the fact and phenomenon and also as base in building the arguments to answer research questions. Built arguments are sourced from conference proceedings, report, protocols, conventions and other literature sources which are processed in qualitative way based on the theories which resulted an explanative argument as a research answer. The result of this study is Vietnam has joined the TPP but in its implementation of intellectual property rights were far from compliance with the TRIPS Agreement. Vietnam has not been able to comply with the commitments of this agreement because it could not provide sufficient protection and strict law enforcement towards the infringements.